Análisis del software de la Tienda Anita para la migración de datos en la nube. - Correa Bedón, Deisler Oliver (2023)
Data migration to the cloud is the process of transferring digital assets, including workloads, data, and applications, to a public or private cloud environment. Cloud migration involves decisions about how you plan to use, maintain, optimize, and control your cloud once the digital migration is complete. Some benefits of cloud migration include cost reduction, scalability, data security, storage, and flexibility. The first step in cloud migration is selecting the workload, starting with a small and effective workload, and then, after gaining some experience in cloud migration, proceeding with increasingly complex workloads. There are cloud migration tools and services available, such as those offered by Amazon AWS and Oracle Cloud Infrastructure.